Pengaruh Kompetensi Profesional dan Kemampuan Mengadopsi Teknologi Digital Terhadap Kualitas Pembelajaran di SD Negeri Gugus Bougenville IV Kecamatan Ulubelu - Dewantoro, Septian; Mu'in, Juhri Abdul; Siswoyo, Siswoyo; Hendrowati, Tri Yuni (Universitas Muhammadiyah Magelang, 2026)
The quality of learning in elementary schools is influenced by teachers’ professional competence and their ability to adopt digital technology; therefore, this study was conducted to analyze the effect of these variables on the quality of learning at State Elementary Schools of Bougenville IV Cluster, Ulubelu District. This study was aimed at determining the partial and simultaneous effects of professional competence and the ability to adopt digital technology on learning quality. A quantitative approach using a survey method was employed involving 83 teachers as respondents. Data were collected through closed-ended questionnaires and analyzed using normality tests, simple linear regression, and multiple linear regression. The results of the normality test indicated that all variables had significance values greater than 0.05, meaning that the data were normally distributed and met the requirements for parametric analysis. The findings revealed that professional competence had a positive and significant effect on learning quality with a regression coefficient of 0.970, a t-value of 6.960, and a significance level of < 0.001, while the ability to adopt digital technology also had a positive and significant effect with a significance value of < 0.05. Simultaneously, both variables had a positive and significant effect on learning quality as indicated by the F-test significance value of < 0.05. It was therefore concluded that the improvement of learning quality can be optimized through the simultaneous enhancement of teachers’ professional competence and their ability to adopt digital technology.